2011
DOI: 10.1155/2011/956169
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Response to the Presence of Polypropylene‐G‐Poly(ethylene glycol) Comb‐Type Graft Copolymers Containing Gold Nanoparticles

Abstract: The aim of this study is to evaluate the soft tissue response of the pure and Au-embedded PPg-PEG. PP-g-PEG2000, PP-g-PEG4000, Au-PP-g-PEG2000, and AuPP-g-PEG4000 were obtained via chlorination of polypropylene and polyethylene glycol in the presence of a base with a “grafting onto” technique. Solvent cast films of these four copolymers with PP as a control group were embedded into five different rats. After 30 days of implantation, microscopic evaluation of inflammation and SEM analysis were done. PP had the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…PP-g-PEG amphiphilic copolymers are water swellable, elastic and biocompatible materials [25,26]. They are suitable to prepare nanocomposite containing metal nano particles or quantum dots [27].…”
Section: Resultsmentioning
confidence: 99%
“…PP-g-PEG amphiphilic copolymers are water swellable, elastic and biocompatible materials [25,26]. They are suitable to prepare nanocomposite containing metal nano particles or quantum dots [27].…”
Section: Resultsmentioning
confidence: 99%
“…Metal nanoparticles such as gold and silver are emerging as attractive biomaterials for targeting soft tissues [27]. Silver, gold, and copper nanoparticles, as well as titanium and zinc oxide nanoparticles, have shown potential therapeutic effects on wound healing [28].…”
Section: Nanoparticles/micelles/lipidsmentioning
confidence: 99%
“…Others showed that silver nanoparticles impregnated in guar gum alkylamine yielded a faster wound-closing rate compared to other positive controls, while histological examination revealed well-organized granulation tissue and epithelialization (Figure 2) [26]. Gold-nanoparticles-embedded biodegradable PEG polymers have been found to possess favorable soft tissue response causing less inflammation as the number of PEG side chain increases ( Figure 3) [27]. Nitric oxide nanoparticles have also demonstrated a broad spectrum of antibacterial properties against both Gram-positive and Gram-negative bacteria [30].…”
Section: Nanoparticles/micelles/lipidsmentioning
confidence: 99%
“…First of all, one should generate hydrocephalus in the tested animal [5,19] or should start the experiment with a mutant hydrocephalic animal which is hard to obtain. Also, to repeat the exact shunt replacement in an animal as in a human being, one should use a bigger canine model such as a dog or a lamb [3,14,38]. Since these animals are vulnerable and hard to obtain, the experiment cannot be designed with higher number of animals because of the ethical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…However, to obtain a wider medical application, nanoparticles can be embedded, and hydrophilic groups can be introduced into this polymer to overcome its hydrophobic character via postpolymerization reactions [2,18,21,22]. We have previously investigated the soft tissue response of polypropylene-grafted polyethylene glycol (PP-g-PEG) amphiphilic graft copolymer film and its nanocomposite version containing gold nanoparticles in rats, under the skin, and found out that these polymer patches have good soft tissue response [14]. In this present study, we have modified the outer and inner surface of the catheter via covering it with PP-g-PEG polymer casts and silver nanoparticle-embedded PP-g-PEG (Ag-PP-g-PEG) casts.…”
Section: Introductionmentioning
confidence: 99%